Economic Ideas and Institutional Change: Evidence from Soviet Economic Discourse 1987-1991 - Joachim Zweynert (Hamburg Institute of International Economics (HWWA), 2005)
In recent years, institutional and evolutionary economists have become increasingly aware that ideas play an important role in economic development. In the current literature, the problem is usually elaborated upon in purely theoretical terms. In the present paper it is argued that ideas are always also shaped by historical and cultural factors. Due to this historical and cultural specificity theoretical research must be supplemented by historical case studies. The paper analyses the shift in ideas that took place in Soviet economic thought between 1987 and 1991. This case study, it is argued, may contribute to our understanding of the links between ideas and institutions. More specifically, it sheds new light on the issue of whether the evolution of economic ideas is pathdependent, so that they change only incrementally, or whether their development takes place in a discontinuous way that can best be compared with revolutions.
Keywords: P27; B24; 330; Economic Ideas; Philosophy of Science; Institutional Change; Historical Specificity; Soviet Union; Transition; Institutioneller Wandel; Sozialphilosophie; Wirtschaftsphilosophie; Sowjetunion